An anomalous origin of 1st lumbrical: a case report - Deb Barma, Mrinmayee; Ahlawat, Harshvardhan (International Journal of Research in Medical Sciences, 2023)
Hand is an organ of prehension. Human hand is an example of revolution in evolution. It is endowed with skilled movements. It consists of different group of muscles, ligaments, joints which are responsible for the fine movements of hand. It also contains neurovascular structures which are the terminal branches of median nerve, ulnar nerve and radial nerve. The terminal branches of ulnar and radial arteries provide the arterial supply. Here, we have reported the variant of lumbrical muscles. Lumbricals perform movements on metacarpophalangeal joints, proximal interphalangeal joints and distal interphalangeal joints. Lumbricals are spindle rich fibres. Variations in the structures present are immensely important for the orthopaedic surgeon, digital transposition surgery, cleft hand surgery etc. Anatomically, incursion of the lumbricals inside the carpal tunnel may lead to work related carpal tunnel syndrome.